Pengaruh Peran Pemerintah Daerah Terhadap Optimalisasi Pendapatan Pajak Daerah - Abdullah Sanduan (P3M Politeknik Negeri Ambon, 2023)
This study aims to know, analyze and obtain empirical evidence about the influence of the Role of Regional Government on the optimization of regional tax revenue. (Survey of Tax Officers of the Ambon City Revenue OfficeThe independent variable in this study is the Role of Regional Government. The dependent variable in this study is the optimization of regional tax revenue. The data in this study is primary data obtained from the distribution of questionnaires directly to all tax collectors of the Ambon City Revenue Office and secondary data as supportThe analysis model used to test the hypothesis is a quantitative analysis in the form of sampling, This analysis is based on data from 40 respondents of the Ambon City Regional Revenue Office through the distribution of questionnaires.The results of this study show that the Role of Regional Government simultaneously has a significant effect on the optimization of regional Tax Revenue partially The Role of Regional Government has a significant effect on the optimization of regional Tax Revenue, in Ambon City.Keywords: Role of Regional Government, Optimization of Regional Tax Revenue